Analysis of Potential Hazards of Work Accidents to Workers Using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) Method in Freight forwarding Companies - Tetelepta, Jerry Octovianus; De Carvalho Belo, Gabriel Barreto (Universitas Pamulang, 2025)
Every activity involving human factors, the environment, and machinery goes through stages of hazard processes. PT. XYZ is a company engaged in providing integrated logistics services. Issues concerning workers' safety an; Health practices remain, as certain work processes pose risks of workplace accidents, resulting in losses for both the company and the workers. The objective of this study is to identify potential Hazards, assess risks, and implement control measures using the HIRARC method. Observations were made on several activities performed by workers or drivers, such as document collection, picking up goods from clients, and delivering them to their destinations. Data collection was conducted through direct observation, interviews, and documentation, including reports on workplace accidents, safety policies, and operational procedures. The research findings identified various types of Hazards and assessed their likelihood of occurrence. Based on these findings, measures must be developed to prevent accidents or mitigate their impact through systematic Risk Control steps.